Practical identification of a glucose-insulin dynamics model. Issue 2 (2020) - Scharbarg, E.; Califano, C.; Carpentier, E. Le; Moog, C.H.
Abstract: Glycemia regulation algorithms which are designed to be implemented in several artificial pancreas projects are often model based control algorithms. However, actual diabetes monitoring is based throughout the world on the so-called Flexible Insulin Therapy (FIT) which does not always cope with current mathematical models. In this paper, we initiate an identification methodology of those FIT parameters from some standard ambulatory clinical data. This issue has an interest per se, or for a further use in any closed-loop regulation system.